Association of the derived neutrophil-to-lymphocyte ratio with cardiovascular and all-cause mortality - Jun Ma; Yingda Song; Shaochen Zhang; Weirong Feng; Ziqing Wei; Zengqiang Shen; Zhiqiang Tong; Xiaoming Bai (PLoS ONE, 2025)
Purpose Accumulating evidence supports the important role of inflammation in disease outcomes. Derived neutrophil-to-lymphocyte ratio (dNLR) is broadly identified as potential prognostic marker in clinical trials or daily clinical practice, but dNLR has never been verified in cardiovascular and all-cause mortality. Methods Overall, 34,392 participants from the National Health and Nutrition Examination Survey (NHANES) were included. The exposure variable was Log-dNLR (dNLR Logarithmic transformation). Participants were categorized according to Log-dNLR quartiles and followed through 31st December 2019. Weighted univariable and multivariable Cox regression were applied to assess the relationship between Log-dNLR evaluated as categorical variables, with cardiovascular and all-cause mortality. Restricted cubic spline (RCS) regression, subgroup analysis, and threshold effect were applied to assess nonlinear relationship between Log-dNLR with cardiovascular and all-cause mortality as well as the effects of special populations. We used multiple sensitivity analyses to reduce selection bias and validate these relationships. Last, the time-dependent weighted receiver operating characteristic (ROC) curve analysis was used to assess predictive accuracy of the Log-dNLR for survival outcomes. Results During a median follow-up duration of 116.90 months, a total of 4,939 all-cause deaths occurred, of which 1,327 were cardiovascular deaths. After adjusting for multiple confounders, compared to the quartile 1, the hazard ratios (HRs) (95% confidence interval, CI) for quartile 4 were 1.38 (95% CI, 1.14–1.68) for cardiovascular mortality and 1.16 (95% CI, 1.06–1.27) for all-cause mortality was identified using RCS regression, with a threshold point of 0.370. Significant differences were observed before and after this threshold point. In addition, there were significant interactions between sex, hypertension status and Log-dNLR (P for interaction = 0.025, 0.005, respectively) for the all-cause mortality risk and significant interactions between age groups, diabetes status and Log-dNLR (P for interaction = 0.007, 0.004, respectively) for the cardiovascular mortality risk. Lastly, ROC analysis revealed that Log-dNLR showed moderate predictive power for all-cause and cardiovascular mortality in the short and long term. Conclusions In summary, elevated dNLR levels are significantly associated with an increased risk of both cardiovascular and all-cause mortality.